RUSSIA’S ENERGY DIPLOMACY: NEW CHALLENGES - Магда, Є.В. (The Journal of V.N. Karazin Kharkiv National University. Series "Issues of Political Science")
Author analyses the conditions of evolution of Russia’s energy policy during last few years. Also he studies the perspectives of its evolution in the nearest time. Author emphasizes the challenges, which Russian state faced today. So, as a result, energy policy is standing at the frontier. Energy policy will definitely change, but it is too early to forecast the way of these changes.